FKBP51 Affects TNF-Related Apoptosis Inducing Ligand Response in Melanoma - Tufano, Martina; Cesaro, Elena; Martinelli, Rosanna; Pacelli, Roberto; Romano, Simona; Romano, Maria Fiammetta (Frontiers in Cell and Developmental Biology, 2021)
Melanoma is one of the most immunogenic tumors and has the highest potential to elicit specific adaptive antitumor immune responses. Immune cells induce apoptosis of cancer cells either by soluble factors or by triggering cell-death pathways. Melanoma cells exploit multiple mechanisms to escape immune system tumoricidal control. FKBP51 is a relevant pro-oncogenic factor of melanoma cells supporting NF-B-mediated resistance and cancer stemness/invasion epigenetic programs. Herein, we show that FKBP51-silencing increases TRAIL-R2 (DR5) expression and sensitizes melanoma cells to TRAIL-induced apoptosis. Consistent with the general increase in histone deacetylases, as by the proteomic profile, the immune precipitation assay showed decreased acetyl-Yin Yang 1 (YY1) after FKBP51 depletion, suggesting an impaired repressor activity of this transcription factor. ChIP assay supported this hypothesis. Compared with non-silenced cells, a reduced acetyl-YY1 was found on the DR5 promoter, resulting in increased DR5 transcript levels. Using Crispr/Cas9 KO melanoma cells, we confirmed the negative regulation of DR5 by FKBP51. We also show that KO cells displayed reduced levels of acetyl-EP300 responsible for YY1 acetylation, along with reduced acetyl-YY1. Reconstituting FKBP51 levels contrasted the effects of KO on DR5-, acetyl-YY1- and acetyl-EP300- levels. In conclusion, our finding shows that FKBP51 reduces DR5 expression at the transcriptional level by promoting YY1 repressor activity. Our study supports the conclusion that targeting FKBP51 increases the expression level of DR5 and sensitivity to TRAIL-induced cell death, which can improve the tumoricidal action of immune cells.